Association between chocolate intake and migraine - Filho, Claudionor Antônio dos Santos; Ferreira , Athyrson de Castro; Barberino , Ana Flávia de Sousa; Anjos, Maíra Marçal dos; Santos, Paula Katherine Marques dos; Santos, Marcus Vinicius Matos dos; Barberino , Ana Paula de Sousa; Ferreira , Gleiciele de Castro (Headache Medicine, 2024)
Background: Migraine, affecting over a billion people globally, necessitates an understanding of its triggers among primary care providers.Objective: This study aims to elucidate the relationship between chocolate intake and migraine attacks.Methods: A literature review was conducted across the PubMed, SciELO, and BvSalud databases using the descriptors "migraine," "trigger," and "chocolate intake." Full-text articles in English or Portuguese were included.Results: Observational studies demonstrate an association between chocolate consumption and migraine attacks. However, randomized controlled trials show no difference between chocolate and placebo in the primary outcome. The high risk of bias in these studies, stemming from questionnaire-based data collection, susceptible to recall and reporting biases, warrants mention.Conclusion: While observational studies suggest an association, robust evidence from randomized controlled trials does not support chocolate intake as a migraine trigger. Further investigation into the chocolate-migraine relationship is crucial, considering the possibility of chocolate cravings being a prodromal symptom of migraine.